The effect of Work Overload and Toxic Workplace on employee performance at a Manufacturing Company in West Java - Della Liani; Dharliana Hardjokowikarto; Juwita Juwita (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to examine and analyze the partial and simultaneous effects of work overload (X1) and a toxic workplace (X2) on employee performance (Y) within a manufacturing company in West Java. The research seeks to clarify how psychological and psychosocial pressures interact to determine workforce productivity in a high-demand industrial environment. This study utilizes an associative quantitative approach rooted in positivism. The population comprises 142 employees with approximately one year of tenure at a manufacturing firm in West Java. Using a simple random sampling technique, a sample size of 105 respondents was established via the Slovin formula with a 5% margin of error. Primary data was gathered using offline questionnaires measured on a 5-point Likert scale. Data analysis was executed via SPSS version 25, encompassing Pearson correlation validity tests, Cronbach's Alpha reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination (R2). The multiple linear regression equation is written as Y = 116.277 + 0.281 X1 - 2.220 X2 The partial test (t-test) reveals that work overload has a positive and significant effect on performance (t-count = 6.770 > t-table = 1.983, p = 0.000 < 0.05). Conversely, a toxic workplace has a severe, highly significant negative effect on performance (t-count = -51.930, absolute value > 1.983, p = 0.000 < 0.05). Simultaneously, the F-test confirms that work overload and a toxic workplace exert a massive combined effect on performance (F-count = 8,324.784 > F-table = 3.09, p = 0.000 < 0.05). The coefficient of determination (R2) is 0.994, demonstrating that the joint model accounts for 99.4% of the variance in employee performance, indicating an exceptionally strong predictive model. At the macroeconomic and regional levels, the manufacturing sector in West Java serves as a critical engine for national economic growth. The findings indicate that while an increase in workload initially boosts short-term output, the presence of a toxic workplace characterized by systemic injustice, interpersonal friction, and poor communication acts as a catastrophic drag on labor productivity, causing a substantial drop-off in performance (B2 = -2.220). For sustainable economic development, manufacturing firms must pivot from raw output maximization to psychosocial environmental management. Mitigating toxic workplace dynamics directly prevents structural labor inefficiencies, lowers high turnover costs, and optimizes human capital development. Promoting a stable and healthy labor ecosystem safeguards regional supply chains and ensures the manufacturing sector's long-term contribution to GDP growth. The novelty of this study lies in its simultaneous structural evaluation of work overload as an intensive physical demand and a toxic workplace as a distinct psychosocial construct, specifically within the labor-intensive manufacturing landscape of West Java. While previous industrial studies focused primarily on physical hazards or generic workloads, this research isolates the profound, non-technical impact of workplace toxicity, proving empirically that an unhealthy psychological climate can heavily undermine and override traditional performance metrics in an industrial factory setting